Prevent, Ideology and Ideological State Apparatus: Analysing Terrorism Prevention Policies Using Althusser's Framework. (January 2022) - Andrews, Sam; Skoczylis, Joshua
The work of Louis Althusser is well regarded in the study of ideology, having been used to analyse the material basis for ideology, and challenging the idea that ideology is simply a product of the mind. Recent advances in counterterrorism have seen many states adopting preventative programmes which are non-violent, and nominally voluntary, attempting to deradicalise or steer subjects away from radical ideologies, in an attempt to stem terrorist recruits. Many of these programmes claim not to be ideological. Prevent, which is the UK's preventative counterterrorism programme, claims not to be ideological, but rather only concerned with stopping extremist ideologies. Using Althusser's Ideological State Apparatus (ISA) framework, this article explores the ideological and material basis of Prevent, arguing that while Prevent assures us of its non-ideological nature, at its core is a programme that is part of the reproductive ideological apparatus of the state.